Fracture-related infection in long bone fractures: A comprehensive analysis of the economic impact and influence on quality of life. Issue 11 (November 2021) - Iliaens, Jorien; Onsea, Jolien; Hoekstra, Harm; Nijs, Stefaan; Peetermans, Willy E.; Metsemakers, Willem-Jan
Highlights: Direct hospital-related healthcare costs of FRI are eight times that of non-FRI long bone fractures. FRI is associated with substantial absenteeism which is almost four times higher compared to non-FRI patients. FRI significantly deteriorates QoL. Abstract: Objectives: Fracture-related infection (FRI) is a feared complication with substantial clinical and economic consequences. The main objective of this study was to compare direct and indirect healthcare costs related to long bone fractures in patients with and without FRI and to assess its impact on the patient's quality of life (QoL). Patients and methods: Between January 2015 and March 2019, 175 patients with FRI were treated at the University Hospitals Leuven (Belgium). Using a matched-pair analysis, patients with an FRI were matched by age, sex, and fracture location (humeral, femoral, or tibial shaft) to a non-FRI cohort treated during the same time period. Clinical and process-related variables, direct hospital-related healthcare costs, and indirect costs due to absenteeism were compared between the two groups. Furthermore, the patient's QoL was evaluated using Patient-Reported Outcomes Measurement Information System (PROMIS) physical function and pain interference. Results: After matched-pair analysis, 15 patients in both the FRI and non-FRI group were included. FRI was associated with direct hospital-related costs being eight times that of non-FRI patients (€ 47, 845 [€ 43, 072–€ 82, 548] vs. € 5, 983 [€ 4, 519–€ 8, 428], p < 0.001). Furthermore, FRI was associated with prolonged absenteeism (340 [340–676] vs. 86 [65–216] days, p = 0.007) and a median indirect cost that was nearly four times that of patients without FRI (€ 77, 909 vs. € 19, 706). Lastly, FRI patients showed significantly poorer outcomes on both physical function (35.6 vs. 48.4, p < 0.001) and pain interference (60.4 vs. 46.3, p < 0.001) PROMIS scales. Conclusion: Direct hospital-related healthcare costs of FRI are eight times that of non-FRI long bone fractures. Total healthcare costs are mainly driven by hospitalisation costs, wherein FRI is associated with prolonged length of stay. To the best of our knowledge, this study is the first to demonstrate that FRI is also associated with substantial absenteeism, which is almost four times higher compared to non-FRI patients. In addition to this economic impact, FRI significantly deteriorates QoL. Generalizing the outcome of this study should be done cautiously due to the small sample size of 15 patients in both the FRI and non-FRI group after matched-pair analysis.